The causal relationship between 5 serum lipid parameters and diabetic nephropathy: a Mendelian randomization study - Liu, Hongzhou; Yao, Xinxia; Wang, Linlin; Liu, Jia; Li, Xiaojing; Fu, Xiaomin; Liu, Jing; Dong, Song; Wang, Yuhan (Frontiers in Endocrinology, 2024)
Background: Serum lipids were found to be correlated with chronic kidney disease and cardiovascular disease. Here, we aimed to research the potential causal associations between five serum lipid parameters and the risk of diabetic nephropathy using several Mendelian Randomization methods.Methods: Genetic data was obtained from the UK Biobank datasets. Causal effects were estimated using multiple MR methods. Heterogeneity and pleiotropy tests were performed.Results: MR analysis revealed that HDL-C and TG exhibited causal associations with diabetic nephropathy (P<0.05). Similar trends were not observed for other lipid parameters.Our research has suggested links between HDL-C, TG and diabetic nephropathy.The findings could contribute to further elucidation of the disease etiology.